ANALISIS KESALAHAN SISWA KELAS VI SD 3 JEKULO DALAM MENYELESAIKAN SOAL CERITA MATERI PECAHAN - Meirina, Ely Noor; Riswari, Lovika Ardana; Kironoratri, Lintang (Universitas Bhinneka PGRI, 2024)
Mathematics word problems written are often considered difficult by students, so there are often many mistakes made by students in solving mathematics story problems. The aim of this research is to analyze the errors made by students in solving word problems on fractions by analyzing the result of students answer. This research inludes qualitative research with the type of case study and was carried out at SD 3 Jekulo. The informants in this research were seven grade at SD 3 Jekulo. The result research of this research were that the students who were used as informants experienced errors in solving story problems on fractions. Mistakes made by students include reading errors, errors in understanding the problems, transformation errors, and errors in writing the final answer. The conclusion of this research is that the seven sixth grade students were proven to have experienced errors in solving fractions questions.